Novel solid-waste-based cementing material and preparation method thereof
By using raw materials such as fly ash, blast furnace slag, calcium carbide slag, Glauber's salt and calcium sulfate, combined with high temperature and cement curing processes, high-strength and low-cost ground polymer blocks were prepared, which solved the problems of low compressive strength and high production costs in the existing technology, and achieved effective utilization of industrial solid waste.
Patent Information
- Application Number
- CN202411754191.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
AI Technical Summary
In the prior art, the compressive strength of the ground polymer blocks prepared with traditional excitants is relatively low, the production cost is high, and there is a safety risk, and industrial solid waste such as calcium carbide slag and Glauber's salt cannot be effectively utilized.
The ground polymer block with good performance is prepared by grinding, sieving and mixing excitants, combined with high-temperature maintenance and cement maintenance processes.
The high-strength performance of ground polymer blocks is achieved, the compressive strength reaches 48.98MPa and the flexural strength is 17.37MPa, which reduces production costs and effectively utilizes industrial solid waste and reduces the mining of natural ore resources.
Smart Images

Figure CN119569360A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of industrial solid waste recycling and construction material preparation, and in particular to a new solid waste-based cementitious material and a preparation method thereof. Background Art
[0002] As a major coal-fired power, coal chemical, industrial silicon, and electrolytic aluminum industrial area, Shihezi produces a large amount of industrial solid waste every year, with an annual output of about 5 million tons of fly ash and about 2.5 million tons of carbide slag. The large-scale production and stacking of various solid wastes not only wastes resources and occupies land, but also brings serious environmental and safety hazards, endangering the ecological environment and people's lives and health. Therefore, how to recycle and utilize the above industrial solid wastes has become a social problem that needs to be solved urgently.
[0003] Geopolymer is a kind of inorganic polymer, an amorphous / quasi-crystalline three-dimensional network structure formed by the polymerization of Si-O tetrahedron and Al-O tetrahedron, and a new type of cementitious material. Geopolymer is usually made of aluminosilicate minerals such as kaolinite and industrial wastes such as fly ash and blast furnace slag as the main raw materials, with water glass (Na2SiO3) and NaOH as activators, and a certain process reaction. Geopolymer is considered to be a promising green and environmentally friendly building material.
[0004] Industrial solid wastes such as fly ash and slag are rich in silicon and aluminum components and are ideal raw materials for preparing geopolymer materials. However, fly ash and slag themselves have low activity and cannot form geopolymers alone. They often need to be added with activators and undergo heating and curing processes to prepare geopolymer materials with good performance. However, the production cost of using traditional activators such as water glass and NaOH to prepare geopolymers is high, and there are safety risks in the transportation of alkali liquid. The main component of carbide slag is Ca(OH)2, and it is alkaline. Glauber's salt (the main component is Na2SO4·10H2O) is a by-product produced in the production process of chemical fiber or chlor-alkali plants. At present, there is not much market and most of it is discarded as waste, which will not only cause environmental problems such as soil and groundwater pollution, but also cause a large waste of resources. Calcium carbide slag and Glauber's salt can be considered to replace traditional alkali activators for the production of geopolymer materials, and can also solve the environmental pollution problems caused by solid waste emissions.
[0005] In the prior art, Chinese invention patent CN112939524A discloses a method for preparing geopolymer blocks activated by carbide slag and sodium sulfate. The geopolymer blocks described in the public document are made of fly ash and desulfurized gypsum as raw materials, and a composite activator is prepared using carbide slag, sodium sulfate, sodium hydroxide, water glass and other conventional alkaline activators to prepare geopolymer blocks. However, the compressive strength of the geopolymer blocks prepared by this method is relatively low.
[0006] Chinese invention patent CN117865532A discloses a method for preparing a freeze-thaw resistant volcanic ash-based polymer activated by composite waste alkali. The method uses volcanic ash and blast furnace slag as raw materials, and uses a triple composite alkali activator of carbide slag-glauber's salt-sodium silicate to activate the synthesis of geopolymer. The geopolymer material prepared by this method has high compressive strength and is relatively stable in a continuous freeze-thaw environment, but the production cost is high.
[0007] Based on the above problems, the present invention provides a new solid waste-based cementitious material and a preparation method thereof, and optimizes the preparation process through factor investigation experiments, aiming to provide a geopolymer building block with good performance, low production cost, simple production process and broad market application prospects. Summary of the invention
[0008] The object of the present invention is to provide a new solid waste-based cementitious material and a preparation method thereof.
[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0010] The solid waste-based novel cementitious material of the present invention comprises the following raw materials: 42-56wt% of fly ash, 14-28wt% of blast furnace slag, 15-25wt% of carbide slag, 0-12wt% of sodium sulfate and 3-5wt% of calcium sulfate.
[0011] Preferably, the new solid waste-based cementitious material of the present invention comprises the following raw materials: 49wt% of fly ash, 21wt% of blast furnace slag, 20wt% of carbide slag, 6wt% of sodium sulfate and 4wt% of calcium sulfate.
[0012] The method for preparing the new solid waste-based cementitious material of the present invention comprises the following steps:
[0013] S1 Pretreatment of raw materials
[0014] Grind and sieve the fly ash and blast furnace slag respectively for later use;
[0015] S2 activator pretreatment
[0016] Grind and sieve carbide slag and sodium sulfate respectively, add calcium sulfate, mix well, and prepare a mixed activator;
[0017] Preparation of S3 Geopolymer Gel Material
[0018] Add the raw material fine powder obtained in step S1 and the mixed activator obtained in step S2 into water, stir and mix them well to obtain a geopolymer gel material;
[0019] S4 Injection Molding
[0020] The geopolymer gel material prepared in the above steps is injected into a mold, and vibrated on a vibration table to remove bubbles, thereby obtaining a geopolymer semi-finished product;
[0021] S5 Curing and demoulding
[0022] The semi-finished geopolymer product obtained in the above steps is placed in a curing box for high-temperature curing, taken out, and placed in a cement curing box for curing. After curing, it is demoulded to obtain the product.
[0023] In the method for preparing the new solid waste-based cementitious material of the present invention, the sieving in steps S1 and S2 is specifically sieving through a 150-250 mesh sieve to obtain fine powder with a particle size of less than 100 μm.
[0024] In the method for preparing the new solid waste-based gelling material of the present invention, the amount of water added in step S3 is 35% to 45% of the total weight of the dry material.
[0025] In the method for preparing the new solid waste-based gelling material of the present invention, the stirring speed in step S3 is 150 to 200 r / min, and the stirring time is 15 to 30 min.
[0026] In the method for preparing the new solid waste-based gelling material of the present invention, the time for vibrating to remove bubbles in step S4 is 5 to 10 minutes.
[0027] In the method for preparing the new solid waste-based cementitious material of the present invention, the conditions for high-temperature curing in step S4 are: temperature of 60-80° C., humidity of 70-100%, and curing time of 12-36 hours.
[0028] In the method for preparing the new solid waste-based cementitious material of the present invention, the curing time in step S4 is 7 to 28 days.
[0029] Preferably, in the method for preparing the new solid waste-based cementitious material of the present invention, the curing time in step S4 is 14 to 28 days.
[0030] Beneficial effects of the present invention:
[0031] Through a series of single factor investigations, the present invention determines that the optimal raw material ratio of the solid waste-based new cementitious material is: 49wt% fly ash, 21wt% blast furnace slag, 20wt% carbide slag, 6wt% sodium sulfate and 4wt% calcium sulfate. Through orthogonal experimental design, the optimal curing conditions of the above solid waste-based new cementitious material are determined as follows: curing temperature of 80°C, humidity of 100%, curing time of 36h, and curing time of 28d. The geopolymer block prepared according to the optimal raw material ratio and the optimal curing process of the present invention has a compressive strength of 48.98MPa and a flexural strength of 17.37MPa, and has good strength performance.
[0032] The present invention uses solid waste fly ash and blast furnace slag as raw materials, and uses carbide slag, sodium sulfate and calcium sulfate as activators to prepare geopolymer materials. The preparation process is simple, and the prepared geopolymer building blocks have good performance. It can not only consume a large amount of industrial solid waste and alleviate the environmental pollution caused by solid waste stacking, but also reduce the exploitation of natural mineral resources such as silicon and aluminum, realize low-cost green production, and has broad market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 Preparation process of new solid waste-based cementitious materials DETAILED DESCRIPTION
[0034] The technical solution of the present invention is described in detail below in conjunction with specific embodiments. The following embodiments are only used for explanation and illustration, and do not constitute a limitation on the technical solution of the present invention.
[0035] Example 1
[0036] A new solid waste-based cementitious material comprises the following raw materials: 49 wt% of fly ash, 21 wt% of blast furnace slag, 20 wt% of carbide slag, 6 wt% of sodium sulfate and 4 wt% of calcium sulfate.
[0037] Example 2
[0038] A new solid waste-based cementitious material comprises the following raw materials: 42 wt% of fly ash, 28 wt% of blast furnace slag, 20 wt% of carbide slag, 6 wt% of sodium sulfate and 4 wt% of calcium sulfate.
[0039] Example 3
[0040] A new solid waste-based cementitious material comprises the following raw materials: 56 wt% of fly ash, 14 wt% of blast furnace slag, 20 wt% of carbide slag, 6 wt% of sodium sulfate and 4 wt% of calcium sulfate.
[0041] Example 4
[0042] A new solid waste-based cementitious material comprises the following raw materials: 49 wt% of fly ash, 21 wt% of blast furnace slag, 15 wt% of carbide slag, 12 wt% of sodium sulfate and 3 wt% of calcium sulfate.
[0043] Example 5
[0044] A new solid waste-based cementitious material comprises the following raw materials: 49 wt% of fly ash, 21 wt% of blast furnace slag, 25 wt% of carbide slag and 5 wt% of calcium sulfate.
[0045] Example 6
[0046] The preparation method of the above-mentioned new solid waste-based cementitious material comprises the following steps:
[0047] S1 Pretreatment of raw materials
[0048] Grind the fly ash and blast furnace slag respectively, pass through a 150-mesh sieve, and set aside;
[0049] S2 activator pretreatment
[0050] Grind carbide slag and sodium sulfate respectively, pass through a 150-mesh sieve, add calcium sulfate, mix well, and prepare a mixed activator;
[0051] Preparation of S3 Geopolymer Gel Material
[0052] The raw material fine powder obtained in step S1 and the mixed activator obtained in step S2 are added into water accounting for 35% of the total weight of the dry materials, and stirred at a speed of 150 r / min for 30 minutes to obtain a geopolymer gel material;
[0053] S4 Injection Molding
[0054] The geopolymer gel material prepared in the above step is injected into a mold, and vibrated on a vibration table for 5 minutes to remove bubbles, thereby obtaining a geopolymer semi-finished product;
[0055] S5 Curing and demoulding
[0056] The semi-finished geopolymer obtained in the above steps is placed in a curing box and cured at 80°C and 100% humidity for 36 hours. It is then taken out and placed in a cement curing box for curing for 28 days. After curing, it is demoulded to obtain the semi-finished geopolymer.
[0057] Example 7
[0058] The preparation method of the above-mentioned new solid waste-based cementitious material comprises the following steps:
[0059] S1 Pretreatment of raw materials
[0060] Grind the fly ash and blast furnace slag respectively, pass through a 250-mesh sieve, and set aside;
[0061] S2 activator pretreatment
[0062] Grind carbide slag and sodium sulfate respectively, pass through a 250-mesh sieve, add calcium sulfate, mix well, and prepare a mixed activator;
[0063] Preparation of S3 Geopolymer Gel Material
[0064] The raw material fine powder obtained in step S1 and the mixed activator obtained in step S2 are added into water accounting for 45% of the total weight of the dry materials, and stirred at a speed of 200 r / min for 15 minutes to obtain a geopolymer gel material;
[0065] S4 Injection Molding
[0066] The geopolymer gel material prepared in the above step is injected into a mold, and vibrated on a vibration table for 5 minutes to remove bubbles, thereby obtaining a geopolymer semi-finished product;
[0067] S5 Curing and demoulding
[0068] The semi-finished geopolymer obtained in the above steps is placed in a curing box and cured at 80°C and 100% humidity for 36 hours. It is then taken out and placed in a cement curing box for curing for 28 days. After curing, it is demoulded to obtain the semi-finished geopolymer.
[0069] Example 8
[0070] The preparation method of the above-mentioned new solid waste-based cementitious material comprises the following steps:
[0071] S1 Pretreatment of raw materials
[0072] Grind the fly ash and blast furnace slag respectively, pass through a 150-mesh sieve, and set aside;
[0073] S2 activator pretreatment
[0074] Grind carbide slag and sodium sulfate respectively, pass through a 150-mesh sieve, add calcium sulfate, mix well, and prepare a mixed activator;
[0075] Preparation of S3 Geopolymer Gel Material
[0076] The raw material fine powder obtained in step S1 and the mixed activator obtained in step S2 are added into water accounting for 35% of the total weight of the dry materials, and stirred at a speed of 150 r / min for 30 minutes to obtain a geopolymer gel material;
[0077] S4 Injection Molding
[0078] The geopolymer gel material prepared in the above step is injected into a mold, and vibrated on a vibration table for 10 minutes to remove bubbles, thereby obtaining a geopolymer semi-finished product;
[0079] S5 Curing and demoulding
[0080] The semi-finished geopolymer obtained in the above steps is placed in a curing box and cured at high temperature for 24 hours at a temperature of 60° C. and a humidity of 70%. It is then taken out and placed in a cement curing box for curing for 28 days. After curing, it is demoulded to obtain the semi-finished geopolymer.
[0081] Example 9
[0082] The preparation method of the above-mentioned new solid waste-based cementitious material comprises the following steps:
[0083] S1 Pretreatment of raw materials
[0084] Grind the fly ash and blast furnace slag respectively, pass through a 150-mesh sieve, and set aside;
[0085] S2 activator pretreatment
[0086] Grind carbide slag and sodium sulfate respectively, pass through a 150-mesh sieve, add calcium sulfate, mix well, and prepare a mixed activator;
[0087] Preparation of S3 Geopolymer Gel Material
[0088] The raw material fine powder obtained in step S1 and the mixed activator obtained in step S2 are added into water accounting for 35% of the total weight of the dry materials, and stirred at a speed of 150 r / min for 30 minutes to obtain a geopolymer gel material;
[0089] S4 Injection Molding
[0090] The geopolymer gel material prepared in the above step is injected into a mold, and vibrated on a vibration table for 10 minutes to remove bubbles, thereby obtaining a geopolymer semi-finished product;
[0091] S5 Curing and demoulding
[0092] The semi-finished geopolymer obtained in the above steps is placed in a curing box and cured at 80°C and 100% humidity for 24 hours. It is then taken out and placed in a cement curing box for curing for 7 days. After curing, it is demoulded to obtain the semi-finished geopolymer.
[0093] Example 10
[0094] The preparation method of the above-mentioned new solid waste-based cementitious material comprises the following steps:
[0095] S1 Pretreatment of raw materials
[0096] Grind the fly ash and blast furnace slag respectively, pass through a 150-mesh sieve, and set aside;
[0097] S2 activator pretreatment
[0098] Grind carbide slag and sodium sulfate respectively, pass through a 150-mesh sieve, add calcium sulfate, mix well, and prepare a mixed activator;
[0099] Preparation of S3 Geopolymer Gel Material
[0100] The raw material fine powder obtained in step S1 and the mixed activator obtained in step S2 are added into water accounting for 35% of the total weight of the dry materials, and stirred at a speed of 200 r / min for 15 minutes to obtain a geopolymer gel material;
[0101] S4 Injection Molding
[0102] The geopolymer gel material prepared in the above step is injected into a mold, and vibrated on a vibration table for 5 minutes to remove bubbles, thereby obtaining a geopolymer semi-finished product;
[0103] S5 Curing and demoulding
[0104] The semi-finished geopolymer obtained in the above steps is placed in a curing box and cured at 80°C and 100% humidity for 12 hours. It is then taken out and placed in a cement curing box for curing for 14 days. After curing, it is demoulded to obtain the semi-finished geopolymer.
[0105] In order to further verify the reliability of the present invention and screen out the best solution, the inventor conducted a series of experiments, as follows:
[0106] 1. Raw materials
[0107] Grade II fly ash, blast furnace slag (grade S95), mirabilite, and carbide slag were all collected from Shihezi area; calcium sulfate (commercially available analytical pure chemical reagent, purity above 95%); tap water. The main chemical components and contents of the experimental raw materials are shown in Table 1.
[0108] Table 1 Main chemical composition and content of raw materials
[0109]
[0110] 2. Preparation of geopolymer materials
[0111] In this study, fly ash and blast furnace slag were used as raw materials, and mixed activators were made of carbide slag, sodium sulfate and calcium sulfate to prepare geopolymer materials. Through the study of the properties of the raw materials, the ratio of raw materials to mixed activators was preliminarily determined to be 7:3. The preparation process of geopolymer blocks is shown in Figure 1 , the operation points are as follows:
[0112] (1) Pretreatment of raw materials: Grind fly ash and blast furnace slag separately, pass through 150-250 mesh sieves, and set aside.
[0113] (2) Pretreatment of the activator: Grind the carbide slag and sodium sulfate separately, pass through a 150-250 mesh sieve, add calcium sulfate, mix well, and prepare a mixed activator.
[0114] (3) Preparation of geopolymer gel material: The raw material fine powder after the above pretreatment and the mixed activator are added into water accounting for 35-45% of the weight of the dry material, and stirred at a speed of 150-200 r / min for 15-30 minutes to obtain the geopolymer gel material.
[0115] (4) Injection molding: The geopolymer gel material prepared in the above steps is injected into a mold and vibrated on a vibration table for 5 to 10 minutes to remove bubbles, thereby obtaining a geopolymer semi-finished product.
[0116] (5) Curing and demoulding: The semi-finished geopolymer obtained in the above steps is placed in a curing box, and cured for 12 to 36 hours at a temperature of 60 to 80° C. and a humidity of 70 to 100%. The semi-finished geopolymer is taken out and placed in a cement curing box for curing for 7 to 28 days. After curing, the semi-finished geopolymer is demoulded.
[0117] 3. Single factor study on optimization of geopolymer block preparation process
[0118] The factors affecting the strength performance of geopolymer blocks mainly include raw material ratio, activator ratio, different water consumption and curing conditions. This study adopted the single factor investigation method to investigate the raw material ratio, activator ratio and different water consumption. The initial curing conditions were curing temperature 80℃, humidity 100%, curing time 36h, and curing time 28d. Geopolymer blocks were prepared according to the process flow under "2. Preparation of geopolymer materials", and the optimal process parameters were determined by measuring the compressive strength and flexural strength of the blocks.
[0119] 3.1 Effect of different raw material ratios on the strength of geopolymer blocks
[0120] Blast furnace slag is rich in silicate and aluminosilicate active substances. Adding it to fly ash can speed up the reaction, reduce the setting time, and improve the strength of the block. However, too high a slag ratio will affect the overall performance of the geopolymer material. Therefore, this study set up different raw material ratios, and explored the effects of different raw material ratios on the strength of geopolymer blocks by measuring the compressive strength and flexural strength of the blocks. The test settings and results of different raw material ratios are shown in Table 2.
[0121] Table 2 Investigation test of different raw material ratios
[0122]
[0123] The results show that the compressive strength of geopolymer blocks increases with the increase of slag proportion, and the flexural strength shows a trend of first increasing and then decreasing with the increase of slag proportion. Taking all factors into consideration, when the mass ratio of fly ash to slag is 7:3, the strength performance of the prepared geopolymer blocks is optimal.
[0124] 3.2 Effect of different activator ratios on the strength of geopolymer blocks
[0125] Fly ash and blast furnace slag are both low-activity geopolymer raw materials that are not easily activated. They usually require the addition of high-concentration alkaline reagents to stimulate their activity. Traditional alkaline activators include water glass (i.e., Na2SiO3) and NaOH, which have good activating effects. However, the production cost of using these traditional activators to prepare geopolymers is high, and there are safety risks in the transportation of alkali solutions. This study uses carbide slag, mirabilite and calcium sulfate to replace traditional activators, and explores the effects of different activator ratios on the strength of geopolymer blocks. The test settings and results of different activator ratios are shown in Table 3.
[0126] Table 3 Investigation test of different activator ratios
[0127]
[0128] The results show that the different proportions of activators designed in this study have good activating effects, and the compressive strength of the prepared geopolymer blocks is higher than 39MPa, and the flexural strength is higher than 11MPa. Among them, the geopolymer blocks prepared by the composite activator composed of 20% carbide slag, 4% calcium sulfate, and 6% mirabilite have the best strength performance.
[0129] 3.4 Effect of different water consumption on the strength of geopolymer blocks
[0130] In the preparation process of geopolymer blocks, different water consumption (i.e., water-binder ratio) is also an important factor affecting the performance of blocks. The appropriate water-binder ratio can make the polymerization reaction of geopolymer materials more complete, improve the bonding effect between materials, and enhance the compressive strength of geopolymer blocks. Therefore, it is necessary to further optimize the optimal water-binder ratio. This study explores the effect of different water-binder ratios on the performance of geopolymer blocks. The test settings and results of different water-binder ratios are shown in Table 4.
[0131] Table 4 Investigation test of different water-binder ratios
[0132]
[0133] From the results, it can be seen that when the water-binder ratio is 0.35, the prepared geopolymer block has a compressive strength of 48.98 MPa and a flexural strength of 17.37 MPa, and the strength performance is optimal.
[0134] 4. Orthogonal experimental design of the effect of different curing conditions on the strength of geopolymer blocks
[0135] Through the single factor investigation test, the results show that the optimal raw material ratio of solid waste-based new cementitious materials is: 49wt% fly ash, 21wt% blast furnace slag, 20wt% carbide slag, 6wt% sodium sulfate and 4wt% calcium sulfate. Geopolymer blocks are prepared according to the above optimal raw material ratio and the process flow under "2. Preparation of geopolymer materials". Orthogonal tests are carried out according to the conditions set in "Table 5" to compare the degree of influence of different curing conditions on the performance of blocks to determine the optimal curing conditions. Four factors that affect the strength performance of blocks, namely curing temperature (A), humidity (B), curing time (C) and curing time (D), are positioned as investigation factors, and orthogonal tests are carried out with 3 levels of each factor based on the preliminary data. The factor level table is shown in Table 5, and the test results and range analysis are shown in Tables 6 to 8.
[0136] Table 5 Orthogonal test factors and levels for curing conditions
[0137]
[0138] Table 6 Results of orthogonal test on curing conditions
[0139]
[0140] Table 7 Analysis of the extreme difference of compressive strength of geopolymer blocks
[0141]
[0142]
[0143] Table 8 Analysis of the extreme difference of flexural strength of geopolymer blocks
[0144]
[0145] From the results, it can be seen that the order of factors affecting the compressive strength and flexural strength of geopolymer blocks is curing temperature > curing time > curing time > humidity. The best curing scheme A3B3C3D3 was screened out through orthogonal experimental design, that is, the curing temperature is 80℃, the humidity is 100%, the curing time is 36h, and the curing time is 28d. The compressive strength of the geopolymer blocks prepared under the optimal curing conditions is 48.98MPa, and the flexural strength is 17.37MPa, with good strength performance.
[0146] Although the present invention has been described in detail above by means of general description, specific implementation methods and experiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A new solid waste-based cementitious material, characterized in that: The invention comprises the following raw materials: 42-56 wt% of fly ash, 14-28 wt% of blast furnace slag, 15-25 wt% of carbide slag, 0-12 wt% of sodium sulfate and 3-5 wt% of calcium sulfate.
2. A new solid waste-based cementitious material, characterized in that: The invention comprises the following raw materials: 49 wt% of fly ash, 21 wt% of blast furnace slag, 20 wt% of carbide slag, 6 wt% of sodium sulfate and 4 wt% of calcium sulfate.
3. The method for preparing a new solid waste-based cementitious material according to claim 1, characterized in that: The steps include: S1 Pretreatment of raw materials Grind and sieve the fly ash and blast furnace slag respectively for later use; S2 activator pretreatment Grind and sieve carbide slag and sodium sulfate respectively, add calcium sulfate, mix well, and prepare a mixed activator; Preparation of S3 Geopolymer Gel Material Add the raw material fine powder obtained in step S1 and the mixed activator obtained in step S2 into water, stir and mix them well to obtain a geopolymer gel material; S4 Injection Molding The geopolymer gel material prepared in the above steps is injected into a mold, and vibrated on a vibration table to remove bubbles, thereby obtaining a geopolymer semi-finished product; S5 Curing and demoulding The semi-finished geopolymer product obtained in the above steps is placed in a curing box for high-temperature curing, taken out, and placed in a cement curing box for curing. After curing, it is demoulded to obtain the product.
4. The method for preparing a new solid waste-based cementitious material according to claim 3, characterized in that: The sieving in steps S1 and S2 is specifically sieving through a 150-250 mesh sieve to obtain fine powder with a particle size of less than 100 μm.
5. The method for preparing a new solid waste-based cementitious material according to claim 3, characterized in that: The amount of water added in step S3 is 35% to 45% of the total weight of the dry material.
6. The method for preparing a new solid waste-based cementitious material according to claim 3, characterized in that: The stirring speed in step S3 is 150-200 r / min, and the stirring time is 15-30 min.
7. The method for preparing a new solid waste-based cementitious material according to claim 3, characterized in that: The time for vibrating in step S4 to remove bubbles is 5 to 10 minutes.
8. The method for preparing a new solid waste-based cementitious material according to claim 3, characterized in that: The conditions for high temperature curing in step S4 are: temperature of 60-80° C., humidity of 70-100%, and curing time of 12-36 hours.
9. The method for preparing a new solid waste-based cementitious material according to claim 3, characterized in that: The curing time in step S4 is 7 to 28 days.
10. The method for preparing a new solid waste-based gelling material according to claim 9, characterized in that: The curing time in step S4 is 14 to 28 days.
Citation Information
Patent Citations
Preparation method of geopolymer building block excited by carbide slag and mirabilite
CN112939524A
Preparation method of freeze-thaw-resistant volcanic ash-based geopolymer excited and synthesized by composite waste alkali
CN117865532A
Cited By
Coal gasification slag-based all-solid waste cementing material based on calcium carbide slag-mirabilite synergistic excitation as well as preparation method and application of coal gasification slag-based all-solid waste cementing material
CN121779023A
Preparation method of filling material based on solid waste-based mining cementing material
CN122079582A